Serving Leadership Model in Stunting Handling Policy in West Papua Province - Paulus Waterpauw (Green Publisher, 2024)
Indonesia faces a significant burden of malnutrition, particularly stunting, despite being the largest economy in Southeast Asia and the 17th largest globally. This study aims to analyze the stunting reduction policy in West Papua Province during the leadership of Acting Governor Paulus Waterpauw in 2022, as well as to evaluate the leadership model demonstrated in addressing the stunting issue, in line with President Joko Widodo's directives to local government officials. The research employed a qualitative approach by analyzing primary and secondary data sources, including policy documents, government reports, and interviews with key stakeholders. The study found that the acceleration of stunting reduction in West Papua during the 2022-2023 period was implemented through five key strategic policies: the issuance of Governor's Regulation No. 17 of 2023, the establishment of the TPPS task force, direct visits (blusukan) to stunting-prone areas, declarations and joint commitments by Regional Government officials, and foster child programs. Paulus Waterpauw's leadership in executing these policies was characterized by a servant leadership model, reflected in qualities such as listening, empathy, conceptualization, foresight, and community-building. These qualities played a crucial role in prioritizing and effectively addressing the stunting issue in West Papua, in accordance with national leadership directives.